1992
DOI: 10.3109/01485019208987714
|View full text |Cite
|
Sign up to set email alerts
|

The Hypoosmotic Swelling Test: An Update

Abstract: The hypoosmotic swelling (HOS) test is a relatively new assay used to evaluate the functional integrity of the sperm's plasma membrane. In fact, more studies have been published on the applicability of the HOS test than any other new sperm indicator. The assay is based on the fact that fluid transport occurs across an intact cell membrane under hypoosmotic conditions until equilibrium is reached. Due to the influx of fluid, the cell will expand and bulge, especially in the tail, and this change can be readily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
74
0
2

Year Published

1996
1996
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(79 citation statements)
references
References 40 publications
3
74
0
2
Order By: Relevance
“…Jeyendran et al (1992) found in dogs that the changes provoked by the hypoosmotic environment could be used for predicting sperm quality. Our findings also show the usability of this test for interpreting the membrane resistance of sperm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jeyendran et al (1992) found in dogs that the changes provoked by the hypoosmotic environment could be used for predicting sperm quality. Our findings also show the usability of this test for interpreting the membrane resistance of sperm.…”
Section: Discussionmentioning
confidence: 99%
“…• The speed of sperm movement was routinely determined using the propulsivity method according to Baker et al (1957 Jeyendran et al (1984Jeyendran et al ( , 1992) was used to determine the membrane integrity of the plasmatic membrane, the membrane on the tail and the consequent morphological changes in the tail for documenting live and dead sperm. The semen was incubated for 30 min in a solution of sodium citrate with 1.35% fructose at 150 mosmoles.…”
Section: Methodsmentioning
confidence: 99%
“…The e ect could have been due to membrane damage as the treated spermatozoa failed to swell in hypoosmotic bu er. The swelling of the sperm tail in hypoosmotic bu er indicates that the sperm membrane is intact and that the sperm are functionally active [8,9]. In addition, Trypan blue staining showed that the treated sperm were not viable, suggesting that the Pongam ia oil also has spermicidal activity.…”
Section: Discussionmentioning
confidence: 99%
“…The e ect of oil on sperm membrane integrity was studied by the hypoosmotic swelling (HOS) test [8,9]. Following treatment with Pongam ia oil as described above, sperm were incubated at 37¯C for 30 min with 1 mL of hypoosmotic solution (7.35 g Na-citrate, 2H 2 O, and 13.51 g fructose in 1 L of H2O having 150 mosmol).…”
Section: At Erials and M Ethodsmentioning
confidence: 99%
“…If no sperm was present in either sample men were advised to seek clinical care for azoospermia. Briefly, sperm viability was evaluated by the hypo-osmotic swelling (HOS) assay (Schrader et al, 1990;Jeyendran et al, 1992). The hyperactivated motility (HTM)-integrated visual optical system (IVOS) computer-aided semen analysis (CASA) platform with video playback (Hamilton Thorne Biosciences, Beverly, MA, USA) was employed to assess eight measures of motility in a 20-µm-depth micro chamber slide (Leja, Nieuw-Vennep, Netherlands).…”
Section: Semen Quality Assessmentmentioning
confidence: 99%